Gender equality in employment: The experience of Kazakhstan. Issue 2 (June 2019) - Buribayev, Yermek A; Khamzina, Zhanna A
No country in the world has achieved full gender equality in labour relations. Kazakhstan has just begun a long way of creating legislative and organizational conditions for equality in the workplace. It is obvious that to create a more equal, gender-sensitive society, a state will require profound changes in perceptions, attitudes, stereotypes, and laws. Facilitating such changes is justified not only from a moral but also from an economic point of view. Today, the requirements for women in society in the performance of labour functions are the same as for men. However, in family and domestic relations, there is a persistence of the gender stereotype of male privileges. There is no change in sectoral gender segregation. Women still make up more than 70% of employees in the health, education, and social services sectors, while women's representation in the financial and public sectors is slightly more than half. Traditionally, these types of sectors are less profitable compared to "male industries, " such as construction, oil and gas, mining, and transport. The level of attracting female labour in innovative, infrastructural, and high-tech projects and programs is very low. The issue of expanding the economic opportunities of rural women, who are denied access to public and state resources and services, remains relevant. In the article, we show the possibilities for ensuring equal employment of men and women in Kazakhstan. The proposals on the improvement of legislation on labour protection and labour conditions and improvement of working conditions are presented, and the possibilities of introducing and expanding flexible forms of employment are considered. Conclusions are drawn on the revision of the list of works prohibiting the use of female labour and ensuring that women have access to types of work that do not pose a danger to women's health due to their automation, technologization, and informatization.